2017
DOI: 10.18549/pharmpract.2017.03.1046
|View full text |Cite
|
Sign up to set email alerts
|

Hospital discharge: What are the problems, information needs and objectives of community pharmacists? A mixed method approach

Abstract: Background:After hospital discharge, community pharmacists are often the first health care professionals the discharged patient encounters. They reconcile and dispense prescribed medicines and provide pharmaceutical care. Compared to the roles of general practitioners, the pharmacists’ needs to perform these tasks are not well known.Objective:This study aims to a) Identify community pharmacists’ current problems and roles at hospital discharge, b) Assess their information needs, specifically the availability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
1
19
2
1
Order By: Relevance
“…Subsequently, patients reported this intentional stop to the community pharmacist during the medication review. The lack of communication between community pharmacists and physicians create issues with care transitions and was identified as a potential risk for patient safety [32,33]. Eggink and colleagues [34] reported that a clinical pharmacist-led discharge service consisting of a medication review, verbal and written information for the patient, and a discharge list with additional information related to medication, decreased the number of prescription errors and medication discrepancies in patients with heart failure.…”
Section: Types Of Medication Discrepanciesmentioning
confidence: 99%
“…Subsequently, patients reported this intentional stop to the community pharmacist during the medication review. The lack of communication between community pharmacists and physicians create issues with care transitions and was identified as a potential risk for patient safety [32,33]. Eggink and colleagues [34] reported that a clinical pharmacist-led discharge service consisting of a medication review, verbal and written information for the patient, and a discharge list with additional information related to medication, decreased the number of prescription errors and medication discrepancies in patients with heart failure.…”
Section: Types Of Medication Discrepanciesmentioning
confidence: 99%
“…5,6 Community pharmacists perceive the lack of communication between hospital and community as a barrier to providing optimal patient care at this point of transition. [6][7][8][9][10] Community pharmacists are often underinformed about changes in patients' medications or medical problems diagnosed during the hospitalization, as discontinued medications or dose changes are not explicitly indicated or rationalized. 10 Community pharmacists provide medication consultation, education and guidance to patients; Hassell et al 11 found that patients often prefer the pharmacists' advice to that of their general practitioner.…”
Section: Introductionmentioning
confidence: 99%
“…16 Other information community pharmacists reported being useful in assessing medication therapy after hospital discharge includes the reason for medication changes, allergies, specifications for "off-label" medication use, laboratory information, or contact information of the prescriber. 7,8 Brühwiler et al 7 found that many community pharmacists judged their ability to manage patient medication therapy, monitor patient progress and outcomes as "(rather) bad" following hospital discharge. There is need for efficient exchange of information at discharge to provide for better provision of care to patients by community pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…addresses significant health systems gaps in communications and transitions of care when patients follow up at community pharmacies following discharge from hospitals. 1 The authors also report on needs and perceptions of community pharmacists in their role to guide optimal patient care. While the authors aptly highlight the need for improvement in care, tangible actions that providers, community pharmacists, and institutions can adopt to accomplish this goal are not fully elaborated.…”
mentioning
confidence: 99%
“… 2 These errors are attributed in part to communication barriers such as inaccessibility of discharge providers, and can lead to increased readmissions, morbidity and mortality. 1 As such, discharging providers must ensure that they actively engage and communicate with community pharmacists. 3 Ensuring easy and reliable access to hospital providers and patient information on discharge by building relationships with local hospitals, and establishing secure next-generation technological systems for bridging communication between community pharmacists and hospital providers should be pursued.…”
mentioning
confidence: 99%